(3GdCSGdjH GdGMUGFjI HGSJNOGe MReI (BMATLABs - (3eMeO YHO GdYGd(B, (3GdfYjejs; (3GdYGfj eRgQ TYHGf(B, s ((3YeGf(B:s (3OGQ hGFd ddfTQ IGdJhRjY(B,s, 2008)
(3jVe gPG GdcJGH eaGgje GMUGFjI , GdMGShH hGdeYdheGJjI , GdeaGgje GdGSGSjI dMReI (Bmatlab (3, JWHjbGJ MReI (Batlab (3aj GdGMUGA GdhUaj , JWHjbGJ MReI (Batlab (3aj GdeNWGWGJ GdGMUGFjI , JWHjbGJ MReI (Batlab (3aj GNJHGQGJ GdaQVjI , JWHjbGJ MReI (Batlab (3aj GdfeGPL GdNWjI JMdjd GdJHGjf , JWHjbGJ MReI (Batlab (3aj GdfeGPL GdNWjI GdJMdjdGJ GdGNQi(B. s
(3HjHdjhZQGajG(B: (3U(B.255-257s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdQjGVjs